Fine needle aspiration cytology of dermal cylindroma - Gupta, Parikshaa (J Cytol, 2014)
In this paper, we have described fine needle aspiration cytology (FNAC) of a rare case of dermal cylindroma. A 40-year-old female presented with a lateral mid-cervical swelling fixed to the skin. FNAC smears showed multiple clusters of small, round to oval cells with hyperchromatic nuclei, inconspicuous nucleoli and scant cytoplasm. In addition, the background showed deposits of basement membrane type material. This was dark magenta colored pinkish globular material. The globules were occasionally surrounded by the basal type of cells. Occasional cells with elongated nuclei were also noted. Cytological diagnosis of skin adnexal tumor possibly cylindroma was offered. Subsequent histopathology of the swelling showed sheets and clusters of cells in a jigsaw puzzle-like fashion. Deposition of abundant basement membrane-like material was noted in between the tumor cells. A diagnosis of cylindorma was offered. FNAC along with the subcutaneous location of the tumor and absence of primary salivary gland tumor may help to diagnose such rare case.